Why We Like to Drink: A Functional Magnetic Resonance Imaging Study of the Rewarding and Anxiolytic Effects of Alcohol - Gilman, Jodi M; Ramchandani, Vijay A; Davis, Megan B; Bjork, James M; Hommer, Daniel W (The Journal of neuroscience, 2008)
People typically drink alcohol to induce euphoria or reduce anxiety, and they frequently drink in social settings, yet the effect of alcohol on human brain circuits involved in reward and emotion has been explored only sparingly. We administered alcohol intravenously to social drinkers while brain response to visual threatening and nonthreatening facial stimuli was measured using functional magnetic resonance imaging (fMRI). Alcohol robustly activated striatal reward circuits while attenuating response to fearful stimuli in visual and limbic regions. Self-ratings of intoxication correlated with striatal activation, suggesting that activation in this area may contribute to subjective experience of pleasure and reward during intoxication. These results show that the acute pharmacological rewarding and anxiolytic effects of alcohol can be measured with fMRI.